EVALUIASI EFEKTIVITAS SISTEM PENGENDALIAN MANAJEMEN DIREKTORAT PEMASARAN PT SEMEN GRESIK (PERSERO) TBK. - , Febriandita Kusuma ([Yogyakarta] : Universitas Gadjah Mada, 2012)
PT Semen Gresik (Persero) Tbk. (Semen Gresik) is one of the biggest cement manufacturing company in Indonesia. Semen Gresik has vision âTo be Leading Cement Company in Indonesia and Southeast Asiaâ. In meeting the vision, Semen Gresik state its strategy focus on revenue management, cost management, capacity management, and increasing competitive advantage. However, based on profitability growth trend, Semen Gresik showed lower growth compared to its peer in Indonesia. It can indicate improper implementation of companyâs strategy. In order to implement strategy, effective and proper management control system is needed. The control system has to be supported by fit organizational structure and responsibility center which in line between responsibility and performance being measured. Strategic plan and budget is needed as a milestone to meet the vision. Effective control system also need to have comprehensive performance evaluation system followed by incentive compensation system as tools in controls and motivates organization performance. Evaluation result of Semen Gresik management control system shows improper application of control system component. Performance evaluation system used is based on financial performance only. Semen Gresik also has no incentive compensation system which can be linked to the performance of each department as responsibility center.